Terapi Murottal Al-Qur'an terhadap Penurunan Tingkat Kecemasan Ibu Postpartum - Lia Fitria; Azizatul Hamidiyah; Anisa F; Arifah A; Arifatul H; Dianatul F (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Pregnancy, childbirth, and postpartum are periods that greatly affect the psychological and social conditions of a woman. In this period, every woman is more at risk for mood disorders, one of which is the postpartum blues. One of the signs of the postpartum blues is anxiety. Al-Qur’an is a method of treatment that has all kinds of programs and data needed to treat various kinds of disorders in the body's cells. Listening to murottal al - qur'an will have a calm and relaxing effect on a person. The purpose of this study was to see the effect of murottal Al-Qur’an therapy on the level of anxiety in postpartum mothers. The research design used was quantitative with pretest and posttest without control design. The sampling technique used purposive sampling with a sample of 30 postpartum mothers and data collection using the ZSAS questionnaire, data processing using the Dependent T-Test. Based on the results of the Dependent T-test showed that there was an effect of murrotal Al-Qur’an therapy on the anxiety level of postpartum mothers (p-value 0.001 <0.05). So that murottal Al-Qur’an therapy can be used as an intervention to overcome anxiety in postpartum mothers.